THE EFFECT OF SELF-EFFICACY ON MOTIVATION TO EXCEL WITH SOCIAL SUPPORT AS A MEDIATING VARIABLE IN STUDENTS IN ISLAMIC BOARDING SCHOOLS - Fauzul Ikhsan; Hasanuddin; Suryani Hardjo (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Achievement motivation is an important factor in students' academic success. The results of observations indicated that students' achievement motivation in the Islamic boarding school tended to decline, as reflected in low academic performance, limited participation in classroom learning, delayed task completion, and decreased enthusiasm for memorizing the Holy Qur'an. This study aimed to examine the effect of self-efficacy on achievement motivation, with social support serving as a mediating variable, among students of Madrasah Aliyah Dayah Terpadu Almuslimun Lhoksukon, North Aceh Regency. The study population consisted of 448 students, with a sample of 200 students selected through random sampling. Data were collected using the Achievement Motivation Scale, the General Self-Efficacy Scale (GSE), and the Multidimensional Scale of Perceived Social Support (MSPSS), and were analyzed using JASP version 0.19.3.0. The results revealed that self-efficacy had a positive and significant effect on achievement motivation (β = 0.508, p < 0.001), self-efficacy had a positive and significant effect on social support (β = 0.417, p < 0.001), and social support had a positive and significant effect on achievement motivation. Furthermore, self-efficacy had a positive and significant indirect effect on achievement motivation through social support as a mediating variable (β = 0.100, p < 0.001).